The role of routine whole volume SPECT reconstruction in comparison to cine raw data in the detection of extracardiac uptake on myocardial perfusion scans - M. Maharaj; N. Korowlay (World Journal of Nuclear Medicine)
The objective of this study was to determine the role of routine whole volume reconstructed single-photon emission tomography (rSPECT) compared to cine raw data to detect extracardiac uptake of Sestamibi (MIBI). In a retrospective study, the myocardial perfusion studies of 426 patients were inspected separately for extracardiac uptake on cine raw data and rSPECT. The acquisition parameters for all the images were done according to departmental protocol. The whole volume SPECT data was selected and processed by HOSEM iterative reconstruction using the HERMES computer software system. The images were assessed by two observers, a student in training and a senior consultant nuclear medicine physician. The overall mean age and standard deviation of the 426 patients at the time of the study was 60 ΁ 12 years. Statistical analysis was performed using the Kappa and McNemars tests. The clinical significance of the extracardiac uptake was evaluated using hospital folders and /or laboratory results after viewing images. rSPECT detected 25 patients (5.9%) and cine raw data identified 18 patients (4.2%) with extracardiac uptake. All the areas of extracardiac uptake noted on cine raw data were seen on the rSPECT images. Only 21 of the 25 patients had complete 5-year clinical follow-up. The value of the clinical significance of the extracardiac uptake was limited due to the study being retrospective. The proportion of positives identified by rSPECT was significantly larger than those identified by cine raw data (P = 0.0082). Although our study demonstrates that rSPECT is more sensitive than cine raw data in detecting extracardiac uptake, it also shows that there is no benefit in routine whole volume rSPECT in daily clinical practice.